Thermal properties enhancement of poly(lactic acid) by corn cob cellulose nanocrystals. Issue 4 (November 2019) - Ng, Wei Keat; Chow, Wen Shyang; Ismail, Hanafi
Cellulose nanocrystals were extracted from agricultural waste corn cob using acid hydrolysis followed by freeze drying. Poly(lactic acid)/corn cob cellulose nanocrystals (PLA/CCNC) composites were prepared using solvent casting. The properties of CCNC were characterized using transmission electron microscope (TEM), zeta potential analyzer, and thermogravimetric analyzer (TGA). The effects of CCNC on the thermal properties of PLA were examined using differential scanning calorimetry (DSC) and TGA. From the SEM and TEM results, the irregular shaped and micron-sized corn cob powder was transformed to needle-like shaped nanocellulose (aspect ratio approximately 30.80) after the acid hydrolysis process. TGA results show that the thermal stability of CCNC is higher than that of corn cob powder. The zeta potential of CCNC is −24.6 mV, which indicates there is a repulsion force between the individual CCNC and making them disperse uniformly and stable in aqueous media. DSC and TGA results show that the crystallinity and thermal stability of PLA were increased by the incorporation of CCNC. This demonstrates that the CCNC is a potential bio-nanofiller with good thermal stability and nucleating-ability for PLA.